STRATEGI MANAJEMEN LINGKUNGAN DALAM RANGKA PENURUNAN KANDUNGAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) PT. PINDO DELI, KARAWANG - Johanes Hendra (Program Studi Manajemen Lingkungan, 2013)
The need for paper today continues to increase, economic growth also means increased forward to improve. The production of industrial paper in National and International market (export) so as to encourage paper mills continue to increase its production. Indonesian paper production in 2011 reached more than 11 million tons. All these activities will result in a positive or negative nature. One of the negative impact that a